An experimental study on the preventive effects of N-acetyl cysteine and ozone treatment against contrast-induced nephropathy - Ozturk,Omur (2018)
Abstract Purpose: To compare the preventive effects of N-acetyl cysteine (NAC), ozone preconditioning and ozone treatment against contrast-induced nephropathy (CIN) in an experimental rat model. Methods: Thirty adult male Wistar rats were randomly distributed into five groups (n=6 for each group). Group I served as control and Group II had only contrast agent, while Group III received NAC and Group IV received intraperitoneal ozone 6 hours before and 6 hours after introduction of contrast agent. Ozone treatment was applied for 5 days after the contrast agent was introduced in Group V. After induction of CIN, groups were compared in terms of serum levels of urea, creatinine, neutrophil gelatinase associated lipocalin, protein carbonyl, total antioxidant capacity (TAC) as well as degree of renal injury at histopathologic level. Results: Groups II-V displayed more obvious histopathological alterations such as hemorrhage and renal tubular injury compared with Group I. TAC (p=0.043) and creatinine (p=0.046) levels increased significantly in Group II after the intervention. In Group III, protein carbonyl level diminished remarkably (p=0.046), while creatinine level was increased (p=0.046) following the intervention. TAC level was higher in Group IV (p=0.028) and Group V (p=0.026) following the procedure. Conclusion: The N-acetyl cysteine and ozone treatment may alleviate the biochemical and histopathological deleterious effects of contrast-induced nephropathy via enhancement of total antioxidant capacity and decreasing oxidative stress.